The impact of delayed adjuvant chemotherapy on survival in gastric cancer patients with and without preoperative chemotherapy - Masataka Shimonosono; Takaaki Arigami; Daisuke Matsushita; Yusuke Tsuruda; Ken Sasaki; Kenji Baba; Takao Ohtsuka (Annals of Gastroenterological Surgery)
Abstract Aim Adjuvant chemotherapy (AC) is the standard treatment for patients with advanced gastric cancer (GC), yet the optimal timing for its initiation remains unclear. Besides, no studies have definitively established when AC should begin in patients receiving preoperative chemotherapy (PC). This study aimed to determine the optimal timing for initiating AC in patients with GC who underwent curative gastrectomy, either with or without PC. Methods A total of 446 patients who underwent curative gastrectomy were evaluated, including 140 who received AC: 72 without PC and 68 with PC. Patients were categorized into two groups based on when they began AC: the early initiation group (within 8 weeks post‐surgery), and the late initiation group (8 weeks or later post‐surgery). Results In the non‐PC cohort, the 3‐year relapse‐free survival (RFS) rates were 71% in the early group versus 56% in the late group (p = 0.49), while the 3‐year overall survival (OS) rates were 94% versus 73% (p = 0.003). Similar trends were observed in the PC cohort; the 3‐year RFS rates were 59% versus 19% (p = 0.002), and the 3‐year OS rates were 69% versus 48% (p = 0.02). Multivariate analysis identified pretherapeutic distant metastasis (p < 0.001) and delayed AC initiation (≥8 weeks) (p = 0.001) as independent predictors of worse prognosis. Conclusion Delayed initiation of AC is associated with significantly poorer postoperative survival in patients with GC, irrespective of whether PC was administered. These findings emphasize the importance of timely AC initiation to improve long‐term outcomes in this patient population.